CRISPR-Cas-Mediated Gene Silencing Reveals RacR To Be a Negative Regulator of YdaS and YdaT Toxins in Escherichia coli K-12 - Gargi Bindal (American Society for Microbiology, 2017)
ABSTRACT Bacterial genomes are rich in horizontally acquired prophages. racR is an essential gene located in the rac prophage that is resident in many Escherichia coli genomes. Employing a clustered regularly interspaced short palindromic repeat (CRISPR)-Cas-based gene silencing approach, we show that RacR is a negative regulator of the divergently transcribed and adjacent ydaS-ydaT operon in Escherichia coli K-12. Overexpression of YdaS and YdaT due to RacR depletion leads to cell division defects and decrease in survival. We further show that both YdaS and YdaT can act independently as toxins and that RacR serves to counteract the toxicity by tightly downregulating the expression of these toxins. IMPORTANCE racR is an essential gene and one of the many poorly studied genes found on the rac prophage element that is present in many Escherichia coli genomes. Employing a CRISPR-based approach, we have silenced racR expression to various levels and elucidated its physiological consequences. We show that the downregulation of racR leads to upregulation of the adjacent ydaS-ydaT operon. Both YdaS and YdaT act as toxins by perturbing the cell division resulting in enhanced cell killing. This work establishes a physiological role for RacR, which is to keep the toxic effects of YdaS and YdaT in check and promote cell survival. We, thus, provide a rationale for the essentiality of racR in Escherichia coli K-12 strains.